Evidencias de validez y fiabilidad de la versión en español del Children’s Depression Inventory-Short en población peruana - Ventura-León, José; Caycho-Rodríguez, Tomás; Tocto-Muñoz, Shirley; Torres-Maldonado, Maryuri; Curahua-Guillén, Karen (Revista de Psicopatología y Psicología Clínica, 2020)
Evidence of validity and reliability of the Spanish version of the Children’s Depression Inventory-Short in Peruvian population Abstract: The objective of this study was to examine the validity evidence of the Children’s Depression Inventory-Short (CDI-S; Kovacs, 1992), in Peruvian school children. A total of 1059 children between 7 and 12 years old participated (Mean = 9.73, SD = 1.23). The results revealed the existence of two factors related to strong loads in the exploratory factor analysis, which were corroborated by confirmatory factor analysis with good goodness-of-fit indices (CFI ≥ .97, RMSEA ≤ .04). The reliability of the CDI-S, calculated with the internal consistency method, was good in both factors (ω > .80). We conclude that the CDI-S is a valid and reliable measure in Peruvian children and should be interpreted as a test with two factors (Dysphoria and Negative self-esteem), which is consistent with previous empirical and theoretical studies. Keywords: Validation; reliability; depression; children. Resumen: El presente estudio tuvo como objetivo examinar evidencias de validez y fiabilidad de la versión en español del Children’s Depression Inventory-Short (CDI-S, Kovacs, 1992), en población peruana. Participaron 1059 niños y niñas entre 7 y 12 años (Media = 9.73, DT = 1.23). Los resultados revelaron la existencia de dos factores relacionados con cargas fuertes en el análisis factorial exploratorio, los cuales fueron corroborados mediante el análisis factorial confirmatorio con buenos índices de bondad de ajuste (CFI ≥ .97, RMSEA ≤ .04). La fiabilidad del CDI-S, calculada con el método de consistencia interna, fue buena en los dos factores (ω > .80). Se concluye que el CDI-S es una medida valida y fiable en niños peruanos y debe ser interpretada como una prueba con dos factores (Disforia y Autoestima negativa), lo cual es coherente con estudios empíricos y teóricos previos. Palabras clave: Validación; fiabilidad; depresión; niños.